2011
DOI: 10.1111/j.2041-1294.2011.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

CdS Quantum Dots in Glass: “Modification of Photoluminescence by Silver Doping”

Abstract: Silicate glasses containing CdS and Ag2O were made by the melt‐quenching method. CdS quantum dots (QDs) were precipitated inside the glass matrix by heat treatment at 570–590 °C for 10 h, and the influence of Ag on photoluminescence (PL) of CdS QDs was investigated. The emission located at 478–493 nm in wavelength originated from the direct recombination of electron/hole pairs was quenched due to charger transfer between Ag and CdS QDs. Modification of PL from CdS QDs by Ag provides potentials toward developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 22 publications
(35 reference statements)
0
32
0
Order By: Relevance
“…[22][23][24][25] The first emissions in both the film at 405 and 384 nm are attributed to the near band edge transition and direct transition from the conduction band to the valence band of TiO 2 . [22][23][24][25] The first emissions in both the film at 405 and 384 nm are attributed to the near band edge transition and direct transition from the conduction band to the valence band of TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25] The first emissions in both the film at 405 and 384 nm are attributed to the near band edge transition and direct transition from the conduction band to the valence band of TiO 2 . [22][23][24][25] The first emissions in both the film at 405 and 384 nm are attributed to the near band edge transition and direct transition from the conduction band to the valence band of TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…16 An additional impure Ti 4 O 7 phase was observed in ''Ag-Au-TiO 2 film'', which was removed after annealing the sample at 600 1C in an inert atmosphere. [14][15][16][17][18][19][20][21][22][23][24][25] The main FTIR peak positions are mentioned in Table S2 of the ESI. This implies that after annealing, the deposited Au nanoparticles entered into the vacant sites of either anatase TiO 2 or rutile TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further increase in annealing temperature leads to the rapid growth of silver nanoparticles and that might have resulted in the quenching of PL intensity for the samples annealed at 550°C and 600°C for 1h 8,31 . An XPS survey spectrum of the cluster clearly shows the [34][35][36][37][38][39][40] . Simo et al reported that the PL intensity of the ion-exchanged (Na + -Ag + ) sample is increases with increase in molecular clustering, which were formed during annealing below the threshold temperature (410°C) 23 .…”
Section: View Article Onlinementioning
confidence: 99%
“…Luminescence properties were in general much studied [43][44][45][46][47][48], and exploited for example for application in solar technologies [49] and rare earth-silver glasses [50][51][52].…”
Section: Properties Of Silver-doped Glassesmentioning
confidence: 99%